2014
DOI: 10.1038/onc.2014.71
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 regulates self-renewal and tumorigenicity of human melanoma-initiating cells

Abstract: Melanoma is one of the most aggressive types of human cancer, characterized by enhanced heterogeneity and resistance to conventional therapy at advanced stages. We and others have previously shown that HEDGEHOG-GLI (HH-GLI) signaling is required for melanoma growth and for survival and expansion of melanoma-initiating cells (MICs). Recent reports indicate that HH-GLI signaling regulates a set of genes typically expressed in embryonic stem cells, including SOX2 (sex-determining region Y (SRY)-Box2). Here we add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
191
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(208 citation statements)
references
References 73 publications
15
191
1
1
Order By: Relevance
“…Nonetheless, our findings do not rule out that SOX2 can exert certain activities in melanoma cells, for instance in isolated cells exposed to varying culture conditions or in the non-physiological environment encountered by human cells upon xenotransplantation into immunocompromised mouse model systems 22 . Of note, studies performed solely in vitro or in combination with xenotransplantation assays provided controversial results, either implicating SOX2 in melanoma cell proliferation or invasion, or also failing to reveal a crucial role in melanoma as in our experiments performed with CRISPR-Cas-mediated knock out cells [20][21][22][23][24] .…”
Section: Sox2 Is Dispensable For Primary Tumor and Metastasis Formationcontrasting
confidence: 74%
See 2 more Smart Citations
“…Nonetheless, our findings do not rule out that SOX2 can exert certain activities in melanoma cells, for instance in isolated cells exposed to varying culture conditions or in the non-physiological environment encountered by human cells upon xenotransplantation into immunocompromised mouse model systems 22 . Of note, studies performed solely in vitro or in combination with xenotransplantation assays provided controversial results, either implicating SOX2 in melanoma cell proliferation or invasion, or also failing to reveal a crucial role in melanoma as in our experiments performed with CRISPR-Cas-mediated knock out cells [20][21][22][23][24] .…”
Section: Sox2 Is Dispensable For Primary Tumor and Metastasis Formationcontrasting
confidence: 74%
“…Tissue microarray (TMA) expression analysis revealed that SOX2 protein is expressed in around 50% of all human melanoma 20,21 . In a recent study, RNAi-mediated silencing of SOX2 led to reduced melanoma sphere self-renewal and tumor growth of xenotransplanted cells, supporting an important role of Sox2 in tumor initiation and tumor maintenance 22 . In other reports, however, knockdown of SOX2 did not affect proliferation of human melanoma cells 20,21,23 .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The shRNA oligonucleotides for SOX2 gene knockdown were designed and synthesized as previously described [23] . Two different shRNA sequences and one scramble sequence as a control were subcloned into plasmid vector pGCsi-H1 following manufacturer's instructions.…”
Section: Silencing Sox2 In Crc Cellsmentioning
confidence: 99%
“…Consequently, the ALDEFLUOR assay has been widely used to isolate CSC subpopulations in various tumors including different types of sarcomas 23,[27][28][29][30][31] . These CSC subpopulations commonly overexpress pluripotency factors such as Sex-determining region Y-Box2 (SOX2), which plays important roles in the regulation of self-renewal and tumorigenicity in CSC subpopulations of several types of cancer [32][33][34][35][36][37] . The process of emergence/evolution of CSC subpopulations from the cell-of-origin in sarcomagenesis has barely been addressed.…”
mentioning
confidence: 99%